Artificial intelligence in the task of segmentation and classification of brain metastases images: current challenges and future opportunities - Hu, Yiheng; Gao, Chao; Wang, Yiren; Wen, Zhongjian; Yang, Cheng; Deng, Hairui; Chen, Shouying; Li, Yunfei; Pang, Haowen; Zhou, Ping; Liao, Bin; Luo, Yan (Frontiers in Neurology, 2025)
Brain metastases (BM) are common complications of advanced cancer, posing significant diagnostic and therapeutic challenges for clinicians. Therefore, the ability to accurately detect, segment, and classify brain metastases is crucial. This review focuses on the application of artificial intelligence (AI) in brain metastasis imaging analysis, including classical machine learning and deep learning techniques. It also discusses the role of AI in brain metastasis detection and segmentation, the differential diagnosis of brain metastases from primary brain tumors such as glioblastoma, the identification of the source of brain metastases, and the differentiation between radiation necrosis and recurrent tumors after radiotherapy. Additionally, the advantages and limitations of various AI methods are discussed, with a focus on recent advancements and future research directions. AI-driven imaging analysis holds promise for improving the accuracy and efficiency of brain metastasis diagnosis, thereby enhancing treatment plans and patient prognosis.